2017
DOI: 10.1002/ase.1722
|View full text |Cite
|
Sign up to set email alerts
|

Improved medical student perception of ultrasound using a paired anatomy teaching assistant and clinician teaching model

Abstract: This study describes a new teaching model for ultrasound (US) training, and evaluates its effect on medical student attitudes toward US. First year medical students participated in hands-on US during human gross anatomy (2014 N = 183; 2015 N = 182). The sessions were facilitated by clinicians alone in 2014, and by anatomy teaching assistant (TA)-clinician pairs in 2015. Both cohorts completed course evaluations which included five US-related items on a four-point scale; cohort responses were compared using Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…This approach of training before reaching a higher competence level on real patients is supported by experts in several studies [17]. Other studies have shown that with minimal instruction, students were able to locate and determine liver size [18]. Similar observations were made in our study where some motivated students went beyond the learning outcomes and started to measure the lobes of the liver with minimal guidance.…”
Section: Discussionsupporting
confidence: 86%
“…This approach of training before reaching a higher competence level on real patients is supported by experts in several studies [17]. Other studies have shown that with minimal instruction, students were able to locate and determine liver size [18]. Similar observations were made in our study where some motivated students went beyond the learning outcomes and started to measure the lobes of the liver with minimal guidance.…”
Section: Discussionsupporting
confidence: 86%
“…Reviewing the qualitative data taken at the time, some students were particularly inspired by being taught directly by radiology trainees, as they felt they could ask more in-depth questions. Several articles discuss that student feedback varies dependent upon the confidence and expertise of staff delivering the sessions [ 15 , 33 ]. For our pilot we enlisted local radiology trainees as faculty during the sessions and to perform the scans.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies overcome this by using anatomists who have been trained to carry out the scans; and whilst some studies have initially shown less favourable feedback with sessions run by less experienced staff [ 15 ], good outcomes have been shown when structured training is put in place for anatomists to develop scanning proficiency [ 35 ]. Other studies have looked at models with paired anatomists and clinicians, thus extending the expertise of the overall faculty for the sessions [ 33 ]. As these models offer more flexibility within the training, future expansion of our own programme will bear these factors in mind.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that ultrasound allows real-time, noninvasive visualization of anatomic structures and their physiological function in vivo, ultrasound has been advocated as an auxiliary educational tool, in particular, for anatomy and physiology teaching ("living anatomy"), as well as for the teaching of physical examinations and basic clinical skills [13][14][15][16][17][18][19][20][21]. There is already consistent evidence that this type of teaching is also very well accepted, wanted, and enjoyed by students [3,14,22], even if the evidence regarding the effect of US on external outcomes is still limited [14,23,24].…”
Section: Discussionmentioning
confidence: 99%